SOLUBILITY OF PETROLEUM COMPOUNDS IN KEROGEN - IMPLICATIONS FOR PETROLEUM EXPULSION - Ritter U. (My University, 2003)
Hildebrand solubility parameters, δ, have been calculated for the most common petroleum compounds, thus establishing a relative solubility scale of petroleum compounds in kerogen. The scale predicts that aromatics as a group are better retained in kerogen than saturates and that there exist large solubility differences within the aromatics. Within saturates, cycloalkanes are better retained than normal alkanes. In order to obtain a picture of direction and magnitude of fractionation, a polymer solution model was coupled with a petroleum generation model. Model results suggest fractionation in the expected direction but not the expected magnitude.